Search for neutron-antineutron oscillations at the Sudbury Neutrino Observatory - Aharmim, Bassam; Dunford, Monica (Physical review, 2017)
Tests on B−L symmetry breaking models are important probes to search for new physics. One proposed model with Δ(B−L)=2 involves the oscillations of a neutron to an antineutron. In this paper, a new limit on this process is derived for the data acquired from all three operational phases of the Sudbury Neutrino Observatory experiment. The search concentrated on oscillations occurring within the deuteron, and 23 events were observed against a background expectation of 30.5 events. These translated to a lower limit on the nuclear lifetime of 1.48×1031 yr at 90% C.L. when no restriction was placed on the signal likelihood space (unbounded). Alternatively, a lower limit on the nuclear lifetime was found to be 1.18×1031 yr at 90% C.L. when the signal was forced into a positive likelihood space (bounded). Values for the free oscillation time derived from various models are also provided in this article. This is the first search for neutron-antineutron oscillation with the deuteron as a target.
Gesehen am 14.12.2018